THE PARENT PERCEPTION OF EARLY SEX EDUCATION IN CHILDREN AT SIMATAHARI VILLAGE, THE SUB DISTRICT OF KOTAPINANG, THE DISTRICT OF LABUHANBATU SELATAN - Fauziah Nasution; Abdul Aziz Rusman; Putra Apriadi (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Sex education is one of the most effective ways to be done in the current generation and parents have a very important role as a place to exchange information with children, especially related to child sexual problems. This research is descriptive with quantitative research with cross-sectional design. The population is parents (father and mother) who have male and female adolescents in Simatahari Village, Kotapinang District, South Labuhanbatu Regency, as many as 55 respondents as respondents. Data analysis in this study only describes the frequency distribution of father and mother characteristics, father's perception and mother's perception of sex education for youth. The results of this study indicate that the majority of parents both father and mother who have adolescents have ages 41-50 years, have education in the junior high school graduation category. the majority of fathers have perceptions of sexual education in the category of negative perceptions of sexual education and the majority of mothers have perceptions of sexual education in the category of negative perceptions of sexual education. It is suggested to fathers and mothers to provide early sex education to their young men and women so that teenagers can avoid the risk of deviant sexual behavior and sexual violence. To parents both fathers and mothers should learn more about sex education in the Islamic view so that fathers and mothers understand better in providing information to their children about early sex education. Keywords: Perception, Parents, Sex Education, Youth